A review of the biology, ecology and control of saddle gall midge, Haplodiplosis marginata (Diptera: Cecidomyiidae) with a focus on phenological forecasting. (30th May 2016) - Rowley, C.; Cherrill, A.; Leather, S.; Nicholls, C.; Ellis, S.; Pope, T.
Abstract: Saddle gall midge Haplodiplosis marginata (Diptera: Cecidomyiidae) is a pest of cereals across Europe. The occasional nature of this pest has resulted in limited and sporadic research activity. There remain important gaps in knowledge due either to a genuine lack of research or to previous research being difficult to access. These knowledge gaps make the development of effective control options difficult. Here, we review the existing literature in an attempt to consolidate the information on H. marginata from research which spans several decades and encompasses many different countries. The current distribution and pest status of this insect are updated, along with the methods of cultural and chemical control available to growers. The biology and life history of the insect are described in detail and the ecological processes governing them are discussed. A forecasting model is presented which allows the emergence of this pest in the UK to be predicted from degree day data, and the potential application of this model in management decisions is discussed. Finally, the areas in most need of further research are identified, along with suggestions of how this information can be used to help develop effective and sustainable management solutions for this pest.